Light backscattering (e.g. reflectance) by ZnO nanorods on tips of plastic optical fibres with application for humidity and alcohol vapour sensing - Lokman, M.Q.; Rahim, H.R.A.; Harun, Sulaiman Wadi; Hornyak, G.L.; Mohammed, W.S. (Institution of Engineering and Technology, 2016)
Relative humidity and alcohol vapour sensing by light backscattering was demonstrated by zinc oxide (ZnO) nanorods grown on tips of plastic optical fibres. Synthesis of ZnO nanostructures was accomplished by the hydrothermal method. A new technique was proposed to extract the backscattered light by ZnO nanostructures. The system was shown experimentally to sense moisture and alcohol vapours. Three ranges of the visible spectrum blue (450-500 nm), green (500-570 nm) and red (610-700 nm) were studied in experiments. Spectral reflectance based on backscattering from ZnO surface structures was used to measure the amount of light backscattered by ZnO nanorods. Results showed that light in the red visible range of the spectrum had higher sensitivity and reflectivity compared with blue and green spectral ranges.